CEO inside debt and investment‐cash flow sensitivity. (22nd January 2015) - Han, Jianlei; Pan, Zheyao
Abstract: This paper provides a new explanation for investment‐cash flow sensitivity from the perspective of CEO inside debt holdings. We examine the effect of CEO pensions and deferred compensation (inside debt) on investment‐cash flow sensitivity for a sample of U.S. manufacturing firms from 2006 to 2012. We find that the firms with higher relative CEO leverage ratios (CEO's debt/equity ratio scaled by the firm's debt/equity ratio) generate higher investment‐cash flow sensitivity. Moreover, one standard deviation increase in the logarithm of the relative CEO leverage ratio enlarges investment‐cash flow sensitivity by 50 per cent. This positive relationship still holds even after we take account of endogeneity and financial constraints.